Ways of war American military history from the Colonial Era to the twenty-first century - Muehlbauer, Matthew S. (Routledge, Taylor & Francis Group, 2014)
From the first interactions between European and native peoples, to the recent peace-keeping efforts in Afghanistan and Iraq, military issues have always played an important role in American history. Ways of War comprehensively explains the place of the military within the wider context of the history of the United States, showing its centrality to American culture and politics. The chapters provide a complete survey of the American military's growth and development while answering such questions as: How did the American military structure develop? How does it operate? And how have historical military events helped the country to grow and develop?